2015
DOI: 10.1016/j.schres.2015.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Early auditory processing evoked potentials (N100) show a continuum of blunting from clinical high risk to psychosis in a pediatric sample

Abstract: Background The N100 is a negative deflection in the surface EEG approximately 100ms after an auditory signal. It has been shown to be reduced in individuals with schizophrenia and those at clinical high risk (CHR). N100 blunting may index neural network dysfunction underlying psychotic symptoms. This phenomenon has received little attention in pediatric populations. Method This cross-sectional study compared the N100 response measured via the average EEG response at the left medial frontal position FC1 to 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Participants with AN displayed a significantly greater N100 latency at baseline, which may be related to a deficit in selective attention [44,45] or to an increased state of arousal [46]. The latter interpretation would be consistent with the correlation of higher N100 latency to a dysfunction in the catecholamine production as evidenced by literature [47].…”
Section: The Baseline Differences In N100 Latency and The Musical Effsupporting
confidence: 59%
“…Participants with AN displayed a significantly greater N100 latency at baseline, which may be related to a deficit in selective attention [44,45] or to an increased state of arousal [46]. The latter interpretation would be consistent with the correlation of higher N100 latency to a dysfunction in the catecholamine production as evidenced by literature [47].…”
Section: The Baseline Differences In N100 Latency and The Musical Effsupporting
confidence: 59%
“…Only a few electrophysiological studies were found, indicating changes in prepulse inhibition (Ziermans et al, 2012) and smaller N100 amplitudes in CHR‐P individuals compared with HC (Gonzalez‐Heydrich et al, 2015, 2016) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…59 Numerous studies have found N1 amplitude deficits in schizophrenia, [60][61][62] which are thought to reflect impairment in auditory perceptual and attentional processing. 63,64 Two studies reported decreased N1 amplitudes in CHR patients compared with controls. 42,63 Moreover, van Tricht et al 65 found that N1 amplitude decreased after 18 months compared with baseline in CHR patients who converted to psychosis, but not in those who did not convert, suggesting that it is a marker of disease progression.…”
Section: Early Auditory Erpsmentioning
confidence: 99%
“…63,64 Two studies reported decreased N1 amplitudes in CHR patients compared with controls. 42,63 Moreover, van Tricht et al 65 found that N1 amplitude decreased after 18 months compared with baseline in CHR patients who converted to psychosis, but not in those who did not convert, suggesting that it is a marker of disease progression.…”
Section: Early Auditory Erpsmentioning
confidence: 99%